Answer:
Step-by-step explanation:
At first you need to turn roots into factors and then multiply the
then you have
f(x) = a(x + 2)(x -5)^2
f(x) = a(x + 2)(x^2 - 10x + 25)
f(x) = a(x^3 - 8x^2 + 5x + 50)
You can use either synthetical or the factor
theorem
f(-2) = a(-8 - 8(4) + 5(-2) + 50) = a(0) = 0.. check, f
=-2
€(5) = a(125 - 8(25) + 5(5) + 50) = a(0) = 0 check, f
= 5 works
Then divide it to the the second multi
And you should get x^2 - 3x - 10 = (x - 5)(x + 2),
where the other two zeros are X =5 , and x=-2